From Religious Authority to Economic Actor: Exploring the Kiai’s Strategic Role in the Economic Empowerment of Pesantren Communities - M. Fawaied Aqiel Fahmy; Abdul Muis; Zainal Abidin (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2024)
This study aims to reveal the strategic role of the kiai in developing and managing community-based economic activities within Islamic boarding schools. Previous research has predominantly emphasized the religious aspects of pesantren, leaving a gap in understanding the role of the kiai as a driver of community-based economic development. The study employs a descriptive qualitative approach, with data collected through in-depth interviews, participatory observation, and document analysis. Data were analyzed thematically through stages of reduction, categorization, and interpretation to achieve a comprehensive understanding. The findings reveal a significant transformation in the role of the kiai from being solely a religious authority to becoming an economic actor who integrates spiritual values with modern management principles. Leadership strategies include optimizing local potential such as productive land, the labor of students, and social networks; establishing clear role distributions within organizational structures; and engaging both students and the community in all stages of the value chain, from planning to distribution. This model not only fosters the economic independence of the pesantren but also strengthens its social function as a center for community empowerment. The synergy between religious values and managerial strategies creates a sustainable and inclusive business ecosystem deeply rooted in local culture. These findings highlight the great potential of pesantren as drivers of community-based economic development that is both productive and morally grounded. Penelitian ini bertujuan mengungkap peran strategis kiai dalam mengembangkan dan mengelola kegiatan ekonomi berbasis komunitas di pesantren. Selama ini kajian tentang pesantren lebih menekankan aspek keagamaan, sehingga masih terdapat kesenjangan dalam memahami peran kiai sebagai motor penggerak ekonomi berbasis masyarakat. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan pengumpulan data melalui wawancara mendalam, observasi partisipatif, dan analisis dokumentasi. Data dianalisis secara tematik melalui tahapan reduksi, kategorisasi, dan interpretasi untuk memperoleh pemahaman yang komprehensif. Hasil penelitian menunjukkan adanya transformasi signifikan peran kiai, dari otoritas keagamaan murni menjadi aktor ekonomi yang memadukan nilai-nilai spiritual dengan prinsip manajemen modern. Strategi kepemimpinan yang diterapkan meliputi optimalisasi potensi lokal seperti lahan produktif, tenaga kerja santri, dan jaringan sosial; pembagian peran yang jelas dalam struktur organisasi; serta pelibatan aktif santri dan masyarakat dalam seluruh rantai nilai usaha produktif, mulai dari perencanaan hingga distribusi. Model ini tidak hanya mendorong kemandirian ekonomi pesantren, tetapi juga memperkuat fungsi sosialnya sebagai pusat pemberdayaan masyarakat. Sinergi antara nilai agama dan strategi manajerial membentuk ekosistem usaha yang berkelanjutan, adaptif terhadap perubahan pasar, serta berakar kuat pada budaya lokal. Temuan ini menegaskan potensi besar pesantren sebagai motor penggerak pembangunan ekonomi berbasis komunitas yang produktif, inklusif, dan bernilai moral.